Pengembangan Sistem Pengelolaan dan Pendanaan Acara dengan Konsep Crowdfunding - Haryaputra Arbisono; Denny Sagita Rusdianto; Aditya Rachmadi (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2021)
Malang City is one of the education city that has a number of students are quite a lot. Many students make the city often to be embraced by various events. In making the event of course they need funds to realize the event project. Some of the ways to earn event funds include selling, doing cooperation through sponsorship, and fundraising. These ways can be impeded so that the events made are not maximal due to the targeted funds are not reached. In addition to funding, the event registration process provided by the Committee is a direct ticketing at a place that is difficult for participants who reside far from the area. Therefore, a fundraising system was developed with the concept of crowdfunding and purchasing tickets to be more efficient in terms of time and effort. This system uses a waterfall model approach. The result is that the system generates twenty-three functional needs which are then tested with unit testing and validation testing which generates valid in all test cases. Non-functional needs are one and tested with SUS with a score of 75. The score has reached the limit of acceptance SUS indicating that the system has been accepted by the user.